Determinants of Participation and Transaction Costs in Rwanda’s Land Markets - Ali, Daniel (World Bank, Washington, DC, 2015)
Land markets play a limited role in subsistence economies with low skill-intensity of agricultural cultivation, equally distributed land endowments and little movement out of agriculture to join the non-farm economy. But, as the economy starts to diversify, the scope for efficiency-enhancing land transfers beyond immediate kin and for longer than just one season assumes significantly greater importance. Lease markets can contribute to the diversification of the economic base in rural areas by allowing those with limited farming skills to take up non-agricultural employment or to migrate temporarily without losing their links to rural areas, and those with comparative advantage in agriculture to increase the size of the land they farm. Land sales, on the other hand, may allow households who want to move into the non-agricultural economy to mobilize the capital that will help them to exploit profitable economic opportunities. Programs aiming to provide higher level of tenure security and better land information systems have often been justified by noting their impact on lowering transaction costs in land markets. Registered land rights make it easier to identify rightful land owners, negotiate and enforce contracts, and reduce the risk of land owners not being able to recover land that they had rented out. This could in turn increase the number of efficiency-enhancing land market transactions; facilitate credit access via the use of land as collateral; and foster structural change and transformation. At the same time, in settings where market imperfections are prevalent, reducing transaction costs in one market will not necessarily improve outcomes across the board.